PENGARUH KUALITAS PRODUK DAN PELAYANAN TERHADAP KEPUASAN KONSUMEN MELALUI MINAT BELI SEBAGAI VARIABEL INTERVENING PADA TOKO KECANTIKAN FITHKA MS GLOW DI MANGARAN SITUBONDO - Feriska, Fera; Kusnadi, Edy; Praja, Yudha (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
ABSTRACT Marketing is an important activity carried out by companies in order to market or sell goods or services to consumers related to products, prices, promotions and distribution or often called the marketing mix. The purpose of this study was to analyze and test the effect of product quality and service in determining consumer satisfaction with purchase intention as an intervening variable. The population in this study are consumers of Fitkha MS Glow in Mangaran Situbondo. The sampling method is determined by probability sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model – Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, indicate that product quality has a significant positive effect on purchase intention, service has a significant positive effect on purchase intention, product quality has a significant positive effect on consumer satisfaction, service has a significant positive effect on consumer satisfaction, purchase intention has a significant positive effect on consumer satisfaction. significant positive on consumer satisfaction. The results of the indirect influence hypothesis show that the product quality variable on consumer satisfaction through purchase intention has a significant positive effect, service on consumer satisfaction through purchase intention has a significant positive effect.